2007
DOI: 10.1007/s10620-006-9457-x
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated Interferon and Ribavirin Failures: Is Retreatment an Option?

Abstract: Currently, there are limited therapeutic options available for chronic hepatitis C (HCV) patients who fail treatment with peginterferon alpha (PEG IFN) + ribavirin (RBV). An option is retreatment with a second course PEG-IFN + RBV. However, the virologic clearance with this option is unknown. Thus, we evaluated the outcome of our cohort of patients with chronic HCV who achieved a sustained viral response when retreated with PEG IFN plus RBV after having no response to an initial course of PEG IFN plus RBV. Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
(15 reference statements)
1
17
0
1
Order By: Relevance
“…Çalışmamızda başlangıç HCV RNA sayısının 600 000 İÜ/ml'den düşük ya da yüksek olmasının KVY oranları üzerinde bir etkisi bulunmamıştır. Çeşitli çalışmalarda yeniden tedaviyle farklı başarı oranları bildirilmektedir (12)(13)(14)(15)(16). Jensen ve arkadaşları (17), PEG IFN-α 2b tedavisine yanıtsız kalan hastaları, ribavirine farklı dozlarda ekledikleri PEG IFN-α 2a ile yeniden 48 ve 72 hafta süreyle tedavi etmişlerdir.…”
Section: İrdelemeunclassified
“…Çalışmamızda başlangıç HCV RNA sayısının 600 000 İÜ/ml'den düşük ya da yüksek olmasının KVY oranları üzerinde bir etkisi bulunmamıştır. Çeşitli çalışmalarda yeniden tedaviyle farklı başarı oranları bildirilmektedir (12)(13)(14)(15)(16). Jensen ve arkadaşları (17), PEG IFN-α 2b tedavisine yanıtsız kalan hastaları, ribavirine farklı dozlarda ekledikleri PEG IFN-α 2a ile yeniden 48 ve 72 hafta süreyle tedavi etmişlerdir.…”
Section: İrdelemeunclassified
“…Of the remaining 42 full-text articles, 30 were excluded because they did not meet inclusion criteria, leaving 14 fulllength papers [3][4][5][6][7][8][9][10][11][12][13][14][15][16] meeting criteria for inclusion in the meta-analysis. Finally, 6 abstracts identified by manual search [17][18][19][20][21][22], were also included, only for the evaluation of the publication bias.…”
Section: Selection Of Trialsmentioning
confidence: 99%
“…The main features of the trials included in the meta-analysis are shown in Table 2 in Appendix. Fourteen, which accounted for 3898 patients, were reported as full papers [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Among the trials, three studies did not report the number of participating centers, while all remaining studies were multicenter trials, with the number of centers ranging from 2 to 133; among these studies 8 reported data on the prevalence of patients with cirrhosis (357/1282 = 27.8%).…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations